1991
DOI: 10.1152/jappl.1991.71.6.2518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cycle exercise on intestinal absorption in humans

Abstract: Intestinal absorption was measured in six trained male cyclists during rest, exercise, and recovery periods with the segmental perfusion technique. Each subject passed a multilumen tube into the duodenojejunum. The experiments consisted of 1) a sequence of 1-h bouts of cycling exercise at 30, 50, and 70% maximal O2 uptake (Vo2max) separated by 1-h rest periods or 2) a 90-min bout at 70% VO2max. The cycling was performed on a constant-load Velodyne trainer. Absorption of water and a 6% carbohydrate-electrolyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 0 publications
1
28
1
3
Order By: Relevance
“…This is not in agreement with two 3-O-methyl-D-glucose recovery studies (Lang, Gisolfi, & Lambert, 2006;Van Nieuwenhoven, Brouns, & Brummer, 1999) suggesting a decrease of CHO absorption during exercise at 70%VO 2max and is not consistent with the evidence available from the intestinal-perfusion studies that reported no effect on CHO absorption in the duodenojejunum (Gisolfi et al, 1991) and in the jejunum (Fordtran & Saltin, 1967) during exercise at 64-78% VO 2max . What could possibly cause an increase of CHO absorption in the jejunum during exercise when the available data from different laboratories are combined?…”
Section: Solute Absorptioncontrasting
confidence: 82%
See 2 more Smart Citations
“…This is not in agreement with two 3-O-methyl-D-glucose recovery studies (Lang, Gisolfi, & Lambert, 2006;Van Nieuwenhoven, Brouns, & Brummer, 1999) suggesting a decrease of CHO absorption during exercise at 70%VO 2max and is not consistent with the evidence available from the intestinal-perfusion studies that reported no effect on CHO absorption in the duodenojejunum (Gisolfi et al, 1991) and in the jejunum (Fordtran & Saltin, 1967) during exercise at 64-78% VO 2max . What could possibly cause an increase of CHO absorption in the jejunum during exercise when the available data from different laboratories are combined?…”
Section: Solute Absorptioncontrasting
confidence: 82%
“…An early study from Fordtran and Saltin (1967) reported no consistent effect of exercise on glucose, fluid, or electrolyte absorption during treadmill running for 1 hr at 64-78% VO 2max . Gisolfi et al (1991) studied intestinal absorption of fluid and CHO during 1-hr bouts of cycle exercise at 30%, 50%, and 70% VO 2max and also found no exercise effect on absorption. However, Barclay and Turnberg (1988) found that water and electrolyte absorption in the jejunum were reduced during 50 min of moderate-intensity (mean heart rate 107 ± 7 beats/min) cycle exercise at 15 km/hr even though the values for water and solute absorption were extremely low.…”
Section: Water Absorptionmentioning
confidence: 98%
See 1 more Smart Citation
“…Rather, it must be due to reduced rates of intestinal absorption of glucose and, by inference, also of water. Indeed the study of Gisolfi et al (25) found that only 37% of fluid perfused into the duodenum and jejunum at rates of 900 ml/hr was absorbed.…”
Section: Posfulafed Causes Of Hyponafremiamentioning
confidence: 99%
“…and that these losses can be considerable especially if the ingested solution has a high (>lo%) carbohydrate content (25,26,82). Furthermore, since most subjects who develop the hyponatremia of exercise do not vomit excessively, hyponatremia can clearly develop even if the translocated sodium is not lost in vomitus.…”
Section: Italics Added)mentioning
confidence: 99%